Ketapang Leaves (Terminalia catappa L.) as Lead (Pb) Bioaccumulators - Ogie, Tommy Bartholomeus; Paat, Frangky Jessy; Fatmona, Shafira Sri Handayani Fatmona (Jurnal Agroekoteknologi Terapan, 2025)
Study This study aims to determine the ability of the leaf plant Ketapang shade tree (Terminalia catappa L.) to accumulate lead (Pb) in Manado City. Purposive sampling is being conducted at three locations. Pb levels in leaves are determined using the Spectrophotometry Atomic Absorption Spectroscopy (AAS) technique. According to research findings, the leaves of Terminalia catappa L. can be considered a bioaccumulator in Manado City. Because of their propensity to absorb metal lead (Pb), the concentrations of Pb on Jalan Piere Tendean, Malalayang Beach Walk, and District Wori range from 0.22-0.44 mg/kg. The highest Pb content was found on Jalan Piere Tendean, which has a high level of density and is rated as high. Recommended: To do advanced research on Pb content in plants, another potential shade as a bioaccumulator or hyperaccumulator in Manado City. Keywords: Terminalia catappa L.; Lead (Pb); Bioaccumulator